Tiens Distributor Communication Strategy In Building Tiens Marketing Network In Samarinda - Hidayah, Nurul (PINISI Discretion Review, 2023)
This research aims to determine the Tiens distributor communication strategy in building the Tiens marketing network in Samarinda City. The research method used is descriptive qualitative with a focus on Communication Strategy research proposed by Wilbur Schramm with the AIDDA model. Data collection techniques were carried out through observation and interviews. The results showed that the communication strategy used by Tiens distributors was through online and offline systems such as endorsing popular artists, holding Grand Open Plans simultaneously in 51 cities in Indonesia by inviting successful Guest Speakers in Tiens business, holding health workshops events and product demonstrations, holding the Tiens Goes To School program by supporting government programs to make them more easily accepted by schools and implementing a communication strategy that is following the established system, namely by promoting business opportunities and their products.